Elevation of IL-8 secretion induced by PEDV infection via NF-κB signaling pathway - Wu, Yang; Wang, Yongrui; Wang, Xuepeng; Li, Mingwei; Yan, Haoxin; Shi, Hongyan; Shi, Da; Chen, Jianfei (Frontiers in Cellular and Infection Microbiology, 2024)
Porcine epidemic diarrhea virus (PEDV) is associated with severe enteritis, which contributes to high mortality in piglets. The aim of this study was to describe molecular mechanisms associated with proinflammatory cytokine(s) production during PEDV infection. We showed that infection of porcine intestine epithelial cell clone J2 (IPEC-J2) with PEDV induces a gradual increase in interleukin 8 (IL-8) production at different time points, as well as infection of Vero E6 with PEDV. The secretion of IL-8 in these two cell lines infected with PEDV is related to the activation of NF-κB. Furthermore, the cells expressing PEDV M or E protein can induce the upregulation of IL-8. These findings suggest that the IL-8 production can be the initiator of inflammatory response by the host cells upon PEDV infection.